2004
DOI: 10.1007/s10549-004-1200-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of matrix metalloproteinases (MMP-2 and MMP-9) in patients with lymph node-negative breast carcinoma

Abstract: Twenty-five to thirty percent of patients with node-negative breast cancer are expected to relapse following surgery, therefore great efforts have been made to identify new prognostic markers that could be useful in defining patients for additional therapy. The expression of MMP-2 and MMP-9 has been associated with high potential of metastasis in several human carcinomas including breast cancer. In the present study we examined the prognostic value of immunoreactive MMP-2/MMP-9 protein in 270 consecutive lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 26 publications
9
109
0
3
Order By: Relevance
“…Our results are in accordance with those of previous reports showing that a high MMP-9 expression correlates significantly with tumoral aggressiveness and poor prognosis (Chantrain et al, 2004;Li et al, 2004;Pellikainen et al, 2004), as well as with other studies where high MMP-2 expression in carcinoma cells, in contrast, has been related to only a few inverse prognostic factors (Talvensaari-Mattila et al, 1998;Nakopoulou et al, 2003) or shown to have no association with clinicopathological parameters in breast cancer (Jones et al, 1999;Hirvonen et al, 2003;Talvensaari-Mattila et al, 2003). It has also been described that as breast cancer progresses, MMP-2 production increases during the early phases, whereas activation of MMP-9 occurs during the late cancerous stage (Liotta and Kohn, 2001), which could explain their different impact on prognosis in clinically detected invasive breast tumours.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with those of previous reports showing that a high MMP-9 expression correlates significantly with tumoral aggressiveness and poor prognosis (Chantrain et al, 2004;Li et al, 2004;Pellikainen et al, 2004), as well as with other studies where high MMP-2 expression in carcinoma cells, in contrast, has been related to only a few inverse prognostic factors (Talvensaari-Mattila et al, 1998;Nakopoulou et al, 2003) or shown to have no association with clinicopathological parameters in breast cancer (Jones et al, 1999;Hirvonen et al, 2003;Talvensaari-Mattila et al, 2003). It has also been described that as breast cancer progresses, MMP-2 production increases during the early phases, whereas activation of MMP-9 occurs during the late cancerous stage (Liotta and Kohn, 2001), which could explain their different impact on prognosis in clinically detected invasive breast tumours.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, two studies (Pellikainen 2004;Gonzalez et al, 2010) provided information about MMP-9 expression in tumor cells and stromal tissues respectively without general result, which we treated independently. Eventually, 15 studies met the inclusion criteria were included (Scorilas et al, 2001;Fan et al, 2003;Li et al, 2004;Pellikainen et al, 2004;Rahko et al, 2004;Li et al, 2006;Mylona et al, 2007;Vizoso et al, 2007;Feng et al, 2008;Wu et al, 2008;Zhao et al, 2008;Tian et al, 2009;Gonzalez et al, 2010;Sullu et al, 2011;Oscar et al, 2012).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[28][29][30] Taken together, the anti-HCC effect of CITED2 is in part mediated through upregulation of IFNA1, TNFRSF1A, TNFRSF25, CASP8, GZMA, and SERPINB5, and down-regulation of TERT and MMP2, which in turn suppresses HCC cell growth (Fig. 7).…”
Section: Cited2 Is a Direct Pparc Target In Hcc/cheung Et Almentioning
confidence: 99%